Elaboración de Chocolate con Espirulina (Spirulina Máxima) Endulzado con Stevia y Frutas Deshidratadas - El Salous, Ahmed; Cadena, Nadia; Mosquera, Corina; Martínez, Tatiana (KnE Engineering, 2018)
The present research is based on elaborating a chocolate bar with spirulina sweetened with stevia and dehydrated fruits, generating an alternative of consumption for the people who like the innovation of the chocolate. The treatments were mainly based on concentrations of cocoa dough (Arriba), dehydrated fruits (pineapple, banana, orange) and esperulin, obtaining as a product of the major sensory acceptance that treatment based on 69% cocoa dough, 20% Dehydrated fruit (pineapple and banana) and 5% spirulina. The Tukey's test was applied to the five percent of the probability in which it was possible to differentiate from the others treatments for its excellent attributes in brightness, sweet taste, fruit flavor and residual sweetness that it possessed. Nutritional results were given as protein with 15.47 g, dietary fiber 11.91 g in 100 grams serving. This indicates that it has a high content of protein, fiber and low concentrations of sucrose; because sugar comes from dehydrated fruits. The microbiological parameters showed that the product complies with the Ecuadorian technical standard NTE INEN 621: 2010, giving evidence that it is fit for human consumption. Key words: Spirulina, dehydrated fruits, stevia, cocoa Arriba.